No Rohingya - Bourny, Yves (Gerakbudaya Enterprise, 2019)
'No Rohingya' interweaves the narrative of the family of Arun, a young Rohingya in Arakan, Burma, with the tales recounted to the children of the community by his elderly grandmother Tameema. As the family itself becomes increasingly ensnared in personal and political persecution, Tameema’s stories, centering on a child raised by wild dogs surviving in a jungle of injustice, provide an alternative world for the memories and morals of the community. As their misfortunes increase and their options narrow, tragedy ultimately permeates both their real and imagined worlds. The stories and experiences in 'No Rohingya' are, unfortunately, solidly grounded in the on-going real life tragedy that faces the Rohingya in Burma. It is both an elegy for a community facing annihilation and a reflection on the nature of history, belonging, and memory.